Effect of pH on Stress Corrosion Cracking of 6082 Al Alloy - C. N. Panagopoulos (Metals, 2018)
In this work, the effect of pH (3, 7 and 10) on the stress corrosion cracking behavior of 6082 aluminum alloy, in a 0.3 M sodium chloride (NaCl) aqueous based solution was investigated. The stress corrosion cracking behavior was studied with slow strain rate testing, whereas failure analysis of the fractured surfaces was used to identify the dominant degradation mechanisms. The experimental results clearly indicated that stress corrosion cracking behavior of this aluminum alloy strongly depends on the pH of the solution. In particular, the highest drop in ultimate tensile strength and ductility was observed for the alkaline pH, followed by the acidic, whereas the lowest susceptibility was observed in the neutral pH environment. This observation is attributed to a change in the dominant stress corrosion cracking mechanisms.